Quartet for 2 violins, viola and violoncello : A minor/a-Moll/La mineur Op. 51/11 No. 11 - Brahms, Johannes (Ernst Eulenburg)
Allegro non tropponAndante moderatonQuasi menuetto, moderato-Allegretto vivacenFinale. Alegro non assai